2018
DOI: 10.1080/23322039.2018.1520423
|View full text |Cite
|
Sign up to set email alerts
|

Bank restructuring and bank efficiency—The case of Vietnam

Abstract: This study examines the link between bank restructuring and bank efficiency in Vietnamese banks employing the Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) approach. The data sample includes 26 commercial banks over the period 1999-2015. Our finding indicates that Vietnamese government's restructuring policies in the first stage have not been beneficial for banks implementing restructuring. Regarding the effect of different restructuring methods, we show that the privatization of state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Research by Gul et al (2011) showed that the greater the credit or financing provided, the greater the ROA. Lee and Hsieh (2013), Vo and Nguyen (2018), Batten and Vo (2019) also found that profitability was an essential indicator for predicting financial difficulties and bank crises. Research by Adelopo et al (2018) andHasanov, Bayramli, andAl-Musehel (2018) exhibited the effect of financing on performance, especially profitability.…”
Section: Relationship Between Financing To Deposits Ratio and Islamic Banks Performancementioning
confidence: 94%
“…Research by Gul et al (2011) showed that the greater the credit or financing provided, the greater the ROA. Lee and Hsieh (2013), Vo and Nguyen (2018), Batten and Vo (2019) also found that profitability was an essential indicator for predicting financial difficulties and bank crises. Research by Adelopo et al (2018) andHasanov, Bayramli, andAl-Musehel (2018) exhibited the effect of financing on performance, especially profitability.…”
Section: Relationship Between Financing To Deposits Ratio and Islamic Banks Performancementioning
confidence: 94%
“…Here, bank efficiency was found to decline during the bank structuring processes, as Vo and Nguyen (2018) showed the different restructuring schemes including the privatization of state-owned commercial banks, state intervention, and mergers and acquisitions (M&As) did not improve efficiency in the long term. Additionally, Vietnam's M&As activities do harm to the return on assets (ROA) while its effects on return on equity (ROE) and net interest margins (NIMs) were not clear (Nguyen and Tran 2019).…”
Section: Bank Structurementioning
confidence: 99%
“…These results were the inverse of Fatima and Shehzad (2014)'s, as they concluded that M&A activities had an impact on ROE, while the influence on ROA was not clear. The role of the government is crucial, as the Vietnam government's restructuring policies in the first stage (1998)(1999)(2000)(2001)(2002)(2003) had not yet supported the banks to implement the restructuring (Vo and Nguyen 2018).…”
Section: Bank Structurementioning
confidence: 99%
“…According to Vo and Nguyen (2018), "Data Envelopment Analysis and Stochastic Frontier Analysis provide a link between bank restructuring and efficiency" in Vietnam's financial institutions. The sample period covers 1999-2015 and includes data from 26 commercial banks.…”
Section: The Financial Performance Impact Of Bank Restructuringmentioning
confidence: 99%